Youth Political Expression Through Tiktok Social Media - Amelia Qory, Wafa; Bayu Mahadian, Adi (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
This research aims to find out the political expression of youth on the @presiden Gen Z account on Tiktok. This research uses descriptive qualitative method. The discourse analysis research method developed by Teun A. Van Dijk. Data was collected through observation, interviews and questionnaires. Data will be accumulated through two different methods, in terms of studying political attitudes towards the Gen Z President's TikTok account, data collection is used directly on the TikTok application, while data collection techniques are used to examine freedom of expression in the form of documentation and observation. Researchers have accumulated data in accordance with research. There are 6 total data and 4 are taken by random sampling. Based on the findings of this research, it can be seen that through Van Dijk's critical discourse analysis, the content in the Gen-Z President's Tiktok account has its own position in accordance with the prevailing discourse structure. However, on the one hand, in the micro discourse structure (rhetoric) of the graphic section, researchers do not find any graphics there. First, this content has a macro structure so it can be said to be a positive structure. While the superstructure in this content is also known there are 5 points that fill in and integrate each other between subtopics so that they are also known to be positive. Further to the positive microstructure to be found in this content is weak in graphics only. Second, this content has a positive macro structure, positive superstructure and negative microstructure in graphics. Third, content 3 has a positive macro structure, positive superstructure and negative microstructure in graphics. Fourth, content 4 has a positive macro structure, positive superstructure and negative microstructure in graphics.